Managing Third-Party Interruptions in Conversations: Effects of Duration and Conversational Role - Bangerter, Adrian; Chevalley, Eric; Derouwaux, Sylvie (My University, 2010)
Dealing with interruptions in collaborative tasks involves two important processes: managing the face of one’s partners and collaboratively reconstructing the topic. In an experiment, pairs were interrupted while narrating personal stories. The duration of the interruption and the conversational role of the target were manipulated. Listeners were more polite than narrators, and longer suspensions caused more effort in reinstatement than short suspensions, but participants were not more polite when suspensions were long.
Keywords: interruptions; collaborative tasks; conversation; narrative